Differences in Stress-Induced Modulation of the Auditory System Between Wistar and Lewis Rats - Szczepek, Agnieszka J.; Dietz, Gunnar P. H.; Reich, Uta; Hegend, Olga; Olze, Heidi; Mazurek, Birgit (Frontiers in Neuroscience, 2018)
Many aspects of stress-induced physiological and psychological effects have been characterized in people and animals. However, stress effects on the auditory system are less explored and their mechanisms are not well understood, in spite of its relevance for a variety of diseases, including tinnitus. To expedite further research of stress-induced changes in the auditory system, here we characterize the reactions to stress using two rat strains: Wistar and Lewis. The animals were stressed for 24 h and subsequently we tested the functionality of the outer hair cells (OHCs) using distortion product optoacoustic emissions (DPOAEs) and auditory neurons using evoked auditory brainstem responses (ABR). Lastly, using Western blot, we analyzed the levels of proteins expressed in inferior colliculi and involved in neuronal plasticity. However, despite some changes detected, we were unable to determine the pattern behind them. We found major differences in the reactions of the two strains: Lewis rats displayed a lowering of their auditory threshold, whereas it was increased in Wistar rats. These functional differences were seen in OHCs of the apical region (low frequencies) and in the auditory neurons (across several frequencies) from day one until two weeks after the experimental stress ended. Wistar and Lewis rats may thus provide models for auditory threshold increase and decrease, respectively, which can both be observed in different patients in response to stress.